10x+-3=4x-21

Simple and best practice solution for 10x+-3=4x-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+-3=4x-21 equation:


Simplifying
10x + -3 = 4x + -21

Reorder the terms:
-3 + 10x = 4x + -21

Reorder the terms:
-3 + 10x = -21 + 4x

Solving
-3 + 10x = -21 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 10x + -4x = -21 + 4x + -4x

Combine like terms: 10x + -4x = 6x
-3 + 6x = -21 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + 6x = -21 + 0
-3 + 6x = -21

Add '3' to each side of the equation.
-3 + 3 + 6x = -21 + 3

Combine like terms: -3 + 3 = 0
0 + 6x = -21 + 3
6x = -21 + 3

Combine like terms: -21 + 3 = -18
6x = -18

Divide each side by '6'.
x = -3

Simplifying
x = -3

See similar equations:

| 11x-3(6-3x)= | | 3x+4(3x-5)=130 | | 3.98i+11.94=23.88 | | 3x+15=2x-5 | | 8-(6-7)=0 | | 8(x+4)=-64 | | 3y+2y=2y-5x | | X+m=no+rq | | 7x-32-9x=8 | | Y=3x^5+3x^3-60x | | -6-(6-6p)=0 | | 4(4-4x)+4=-2x+2-14x | | 5-9+x=65 | | -4=4(3-b) | | 6x+3(4x+2)=96 | | -4x+6=6x+16 | | 9x-1=2x-12 | | -14=3x+10 | | 3x*-5=4x*-2 | | 10+x-6=2 | | 3h-6=24 | | 6i-4=2i+24 | | 15x+3x-4=14whatisx | | 3x+5x+5=11+10x+6 | | 6(x+3)+7-x=4x(x+3) | | S-15=15.19 | | 8X-14=7X+9 | | 9(x-2)=72 | | 3(2x-5)+6=4x+7 | | 4(x-3)=x-5 | | 5d+15-2d-10=11 | | 256+5546=x |

Equations solver categories